The Optimization of Forced Ventilation Parameters on Blind Roadway Based on Fluent Numerical Simulation - Fuliang, Jiang; Shuai, Zhang; Zengguang, Yang; Xiangyang, Li; Ming, Li; Wenchao, Yang; Xiaoli, Wang (2017 10th International Symposium on Computational Intelligence and Design (ISCID), 2017)
In view of the fact that toxic and harmful gases are not easily discharged after blasting on the mining face of blind roadway in underground mine, it is necessary to optimize the forced ventilation parameters of this kind roadway. Taking a Fluorite mine as example, the distribution and diffusion law of toxic and harmful gases after blasting were analyzed by using Fluent software through the numerical simulation of component transportation. Besides, the numerical simulation was carried out to study some optimum conditions, such as design of the fan outlet, diameter of the air duct and magnitude of the wind speed. The study results indicates that: the best distance between the fan and digging surface is about 10m; the fan diameter should be no more than 400mm; the wind speed of the fan outlet should be kept within the range between 8m/s to 10m/s. The above conclusions can provide reference and basis for technical renovation of the mine ventilation.